Heterocyclic sterol probes for live monitoring of sterol trafficking and lysosomal storage disorders - Králová, Jarmila; Jurášek, Michal; Krčová, Lucie; Dolenský, Bohumil; Novotný, Ivan; Dušek, Michal; Rottnerová, Zdeňka; Kahle, Michal; Drašar, Pavel; Bartůněk, Petr; Král, Vladimír (Scientific reports, 2018)
The monitoring of intracellular cholesterol homeostasis and trafficking is of great importance because their imbalance leads to many pathologies. Reliable tools for cholesterol detection are in demand. This study presents the design and synthesis of fluorescent probes for cholesterol recognition and demonstrates their selectivity by a variety of methods. The construction of dedicated library of 14 probes was based on heterocyclic (pyridine)-sterol derivatives with various attached fluorophores. The most promising probe, a P1-BODIPY conjugate FP-5, was analysed in detail and showed an intensive labelling of cellular membranes followed by intracellular redistribution into various cholesterol rich organelles and vesicles. FP-5 displayed a stronger signal, with faster kinetics, than the commercial TF-Chol probe. In addition, cells with pharmacologically disrupted cholesterol transport, or with a genetic mutation of cholesterol transporting protein NPC1, exhibited strong and fast FP-5 signal in the endo/lysosomal compartment, co-localizing with filipin staining of cholesterol. Hence, FP-5 has high potential as a new probe for monitoring cholesterol trafficking and its disorders.
Keywords: buněčná membrána; Microscopy, Fluorescence; Cholesterol; Humans; cholesterol; sloučeniny boru; fluorescenční mikroskopie; lidé; Lysosomal Storage Diseases; Pyridines; buněčné linie; biologický transport; fluorescenční barviva; Cell Line; Fluorescent Dyes; steroly; pyridiny; Boron Compounds; Sterols; Cell Membrane; lyzozomální nemoci z ukládání; Biological Transport